Prevalence and correlates of stocking up on drugs during the COVID-19 pandemic: Data from the C3PNO Consortium. (1st December 2022) - King, L.; Hayashi, K.; Genberg, B.; Choi, J.; DeBeck, K.; Kirk, G.; Mehta, SH; Kipke, M.; Moore, RD; Baum, MK; Shoptaw, S.; Gorbach, PM; et al.
Abstract: Background: Data from the COVID-19 pandemic describes increases in drug use and related harms, especially fatal overdose. However, evidence is needed to better understand the pathways from pandemic-related factors to substance use behaviours. Thus, we investigated stockpiling drugs among people who use drugs (PWUD) in five cities in the United States and Canada. Methods: We used data from two waves of interviews among participants in nine prospective cohorts to estimate the prevalence and correlates of stockpiling drugs in the previous month. Longitudinal correlates were identified using bivariate and multivariate generalized linear mixed-effects modeling analyses. Results: From May 2020 to February 2021, we recruited 1873 individuals who completed 2242 interviews, of whom 217 (11.6%) reported stockpiling drugs in the last month at baseline. In the multivariate model, stockpiling drugs was significantly and positively associated with reporting being greatly impacted by COVID-19 (Adjusted Odds Ratio [AOR]= 1.21, 95% CI: 1.09–1.45), and at least daily use of methamphetamine (AOR = 4.67, 95% CI: 2.75–7.94) in the past month. Conclusions: We observed that approximately one-in-ten participants reported stocking up on drugs during the COVID-19 pandemic. This behaviour was associated with important drug-related risk factors including high-intensity methamphetamine use. While these correlations need further inquiry, it is possible that addressing the impact of COVID-19 on vulnerable PWUD could help limit drug stockpiling, which may lower rates of high-intensity stimulant use. Highlights: Among 1873 people who use drugs in the United States and Canada, 12% reported stocking up on drugs during COVID. Stocking up on drugs was positively associated with high-intensity use of methamphetamine. People stocking up on drugs were also more likely to self-report being greatly impacted by the pandemic.